Deep vein thrombosis and pulmonary embolism in cirrhotic patients: Systematic review - Aggarwal, Ashish (Baishideng Publishing Group Inc, 2014)
Patients with liver cirrhosis were traditionally believed to be protected against development of blood clots. Lately, studies have shown that these patients may probably be at an increased risk of venous thrombotic complications. Although the hemostatic changes in the chronic liver disease patients and the factors that may predict bleeding vs thrombotic complications remains an area of active research, it is believed that the coagulation cascade is delicately balanced in these patients because of parallel reduced hepatic synthesis of pro and anticoagulant factors. Thrombotic state in cirrhotic patients is responsible for not only portal or non-portal thrombosis [deep vein thrombosis (DVT) and pulmonary embolism (PE)]; it has also been associated with progression of liver fibrosis. The use of anticoagulants in cirrhosis patients is a challenging, and often a scary situation. This review summarizes the current literature on the prevalence of venous thrombosis (DVT and PE), risk factors and safety of prophylactic and therapeutic anticoagulation in patients with chronic liver disease.